The Effect of Education on Knowledge Levels of Proper Tooth Brushing Among Grades 1–3 Students of Banawa Elementary School, Donggala Regency - Andi Mariani; Hayati Palesa; Rahma Badaruddin; Warihan Unok; Ni Wayan Sridani (International Journal of Medicine and Health, 2025)
Teeth and mouth are the first part of the digestive system, where germs and bacteria can enter and cause health problems. Teeth are also part of the body. Tooth decay can affect the health of other body parts, which can disrupt daily activities. Brushing your teeth plays a very important role in preventing the development of bacteria that can cause tooth decay. Therefore, effective educational efforts are needed to care for teeth by brushing your teeth at least twice a day at the right time, in the morning after breakfast and at night before bed. The behavior of eating sticky and sweet foods can affect the occurrence of tooth decay. One method that is considered effective is education that can increase knowledge about how to brush your teeth properly. The purpose of this study was to analyze the effect of providing education on how to brush your teeth properly and correctly to increase the knowledge of elementary school children. This study used a quasi-experimental research method (Quasi Experimental Design), a pre-experimental design with a pre-post design Single group that is quantitative. The population in this study was 55 people. The research sample was 35 people using the Slovin formula with a margin of error (0.1). with a significance level of p <0.05.